2022
DOI: 10.3389/fimmu.2022.845678
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3-Regulated PGE2 Production by Microglia Induces Phobic Anxiety Susceptibility After Stroke and Pointedly Exploiting a Signal-Targeted Gamma Visual Stimulation New Therapy

Abstract: BackgroundPhobic anxiety present after stroke (called poststroke anxiety, PSA) can hamper the rehabilitation of patients and disrupt their usual activities. Besides, the symptoms and mechanisms of PSA are different from those in nonstroke populations that have generalized anxiety disorder. What’s more, the treatment approaches for phobic anxiety are confined to unitary or general methods with poor efficiency.MethodsBehavioural test screen combined bioinformatics analysis explored molecular changes between gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…It has been reported Caspase-3 is known that the proapoptotic protein Bax and the anti-apoptotic protein Bcl-2 can migrate from the cytoplasm to mitochondria, which are distributed in a manner that is consistent with the mitochondrial release of cytochrome C and caspase [20,27]. The mitochondrial apoptotic pathway plays an essential role in neuronal injury [28,29], and TAT-PEP inhibited neuronal apoptosis after ischemic stroke by upregulating Bcl-2 expression and reducing Bax expression. The apoptotic proteins on the mitochondrial membrane, such as Bad and Bax, lead to the opening of the mitochondrial permeability transition pore and the release of cytochrome C or apoptosis factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported Caspase-3 is known that the proapoptotic protein Bax and the anti-apoptotic protein Bcl-2 can migrate from the cytoplasm to mitochondria, which are distributed in a manner that is consistent with the mitochondrial release of cytochrome C and caspase [20,27]. The mitochondrial apoptotic pathway plays an essential role in neuronal injury [28,29], and TAT-PEP inhibited neuronal apoptosis after ischemic stroke by upregulating Bcl-2 expression and reducing Bax expression. The apoptotic proteins on the mitochondrial membrane, such as Bad and Bax, lead to the opening of the mitochondrial permeability transition pore and the release of cytochrome C or apoptosis factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the model of post-stroke anxiety, HDAC3 was upregulated in the microglia of damaged cortex, which induced p65 deacetylation and the subsequent activation of NF-κB signaling involved in prostaglandin synthesis. Prostaglandin E 2 released by cortical microglia could act on EP2 in the amygdala, potentially leading to the susceptibility to anxiety [ 207 ]. Discs large homolog 1 (Dlg1) is an adaptor protein regulating the activation of microglia, and Dlg1 knockout inhibited NF-κB and MAPK pathways in the microglia, leading to the alleviation of LPS-induced depression [ 208 ].…”
Section: Microglia In Behavioral and Neuropsychiatric Disordersmentioning
confidence: 99%
“…Gamma entrainment has been investigated in treatment of various CNS diseases [ 316 , 317 ]. In AD models, gamma entrainment enhanced microglial phagocytotic activity [ 318 , 319 ]; in post-stroke models, gamma entrainment inhibited the pro-inflammatory activation of microglia and ameliorated anxiety susceptibility [ 207 ]. However, there is emerging controversy about the neuroprotective effect of gamma entrainment, and the gamma-band visual stimulation may be aversive for mice [ 320 ].…”
Section: Future Perspectives For the Fieldmentioning
confidence: 99%
“…Lastly, Zhu et al. (2022) found that visual gamma entrainment can ameliorate neurological conditions other than AD. In mice exposed to post‐stroke stress, the authors reported that visual gamma stimuli were able to trigger the downregulation of histone deacetylase 3 (HDAC3), cyclooxygenase‐1 (COX1) and EP2 in the amygdala, which can alleviate susceptibility to anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%